CAREC gender strategy 2030. (Country diagnostic studies., 2020)
The Central Asia Regional Economic Cooperation (CAREC) member countries face common challenges to improving gender equality and women empowerment. The coronavirus disease (COVID-19) pandemic also aggravated existing inequalities. This document complements national plans in line with the CAREC 2030 strategic framework road map to gender mainstreaming in (i) economic and financial stability, (ii) trade, tourism, and economic corridors, (iii) infrastructure and economic connectivity, (iv) agriculture and water, and (v) human development.